Effect of Rust (Uromyces Phaseoli Var. Vignae) Infection on Photosynthetic Efficiency, Growth and Yield Potentials of Cowpea (Vigna Unguiculata L. Walp) in an Open Field System (Global Journal of Science Frontier Research, 2020)
Cowpea rust fungus affects photosynthetic rate and physiological performance of the host plant through the induction of structural changes in the host cell. The study assessed the effects of rust fungus on net photosynthetic efficiency and yield performance of cowpea genotypes under field conditions. The experiment was conducted in the minor cropping season following a randomized complete block design outlay with three replications. Chlorophyll fluorescence of healthy leaves and rust-infected leaves of each cowpea genotype was determined by a non-destructive method. Rust disease severities of the infected leaves were assessed based on a diagrammatic scale. The effect of rust on the net photosynthetic rate was quantified by the model Px / Po = (1 -x) β . Growth and yield traits of the cowpea genotypes and correlation between seed yield and photosynthetic efficiency were determined. The cowpea genotypes responded differently to rust infection as expressed in net photosynthetic rates, growth, and yield. The pathogen impaired photosynthetic efficiency of leaf tissue beyond the observed diseased leaf area. Seed yield was more closely related to the β estimate than that observed for the relative net photosynthetic rate.
Keywords: cowpea; rust pathogen; disease severity; photosynthetic rate; growth; yield